Unanticipated Geochemical and Microbial Community Structure under Seasonal Ice Cover in a Dilute, Dimictic Arctic Lake - Schütte, Ursel M. E.; Cadieux, Sarah B.; Hemmerich, Chris; Pratt, Lisa M.; White, Jeffrey R. (Frontiers in Microbiology, 2016)
Despite most lakes in the Arctic being perennially or seasonally frozen for at least 40% of the year little is known about microbial communities and nutrient cycling under ice cover. We assessed the vertical microbial community distribution and geochemical composition in early spring under ice in a seasonally ice-covered lake in southwest Greenland using amplicon-based sequencing that targeted 16S rRNA genes and using a combination of field and laboratory aqueous geochemical methods. Microbial communities changed consistently with changes in geochemistry. Composition of the abundant members responded strongly to redox conditions, shifting downward from a predominantly heterotrophic aerobic community in the suboxic waters to a heterotrophic anaerobic community in the anoxic waters. Operational taxonomic units (OTUs) of Sporychtiaceae, Commamonadaceae, and the SAR11 Clade had higher relative abundances above the oxycline and OTUs of Methylobacter, Lentisphaera, and purple sulfur bacteria (PSB) below the oxycline. Notably, a 13-fold increase in sulfide at the oxycline was reflected in an increase and change in community composition of potential sulfur oxidizers. Purple non sulfur bacteria were present above the oxycline and green sulfur bacteria and PSB coexisted below the oxycline, however PSB were most abundant. For the first time we show the importance of PSB as potential sulfur oxidizers in an Arctic dimictic lake.